Ultrasound-Guided Versus Computed Tomography-Controlled Facet Joint Injections in the Lumbar Spine: A Prospective Randomized Clinical Trial. Issue 4 (1st July 2007) - Galiano, Klaus; Obwegeser, Alois Albert; Walch, Claudia; Schatzer, Reinhold; Ploner, Franz; Gruber, Hannes
Abstract : Background and Objectives: Facet joint injections are widely used for alleviation of back pain. Injections are preferentially performed as fluoroscopy or computed tomography (CT)-controlled interventions. Ultrasound provides real-time monitoring, does not produce ionizing radiation, and is broadly available. Methods: We studied feasibility, accuracy, time-savings, radiation doses, and pain relief of ultrasound-guided facet joint injections versus CT-controlled interventions in a prospective randomized clinical trial. Forty adult patients with chronic low back pain were consecutively enrolled and evenly assigned to an ultrasound or a CT- group. Results: Eighteen subjects from the group randomized to ultrasound were judged to be feasible for this type of approach. In 16 of them the facet joints were clearly visible and all of the associated facet joint injections were performed correctly. The duration of procedure and radiation dose was 14.3 ± 6.6 minutes and 14.2 ± 11.7 mGy˙cm in the ultrasound group, and 22.3 ± 6.3 minutes and 364.4 ± 213.7 mGy˙cm in the CT group. Both groups showed a benefit from facet joint injections. Conclusions: The ultrasound approach to the facet joints in the lumbar spine is feasible with minimal risks in a large majority of patients and results in a significant reduction of procedure duration and radiation dose.